Pemikiran dan Praksis Dakwah Sufistik M. Fethullah Gülen - Sokhi Huda (Islamica: Jurnal Studi Keislaman, 2017)
This article discusses a study of the existence of Sufism of the contemporary Islamic preaching of M. Fethullah Gülen. The thought of Gülen’s Islamic preaching originates from his view of Sufism as the spiritual life and the journey of a human life to achieve happiness in this world and hereafter. This thinking evolves and can be accepted by the global community in the contemporary era. This thought disseminates the ideas of love, tolerance, and pluralism and receives attention from over 160 countries. Then, the praxis of the Gülen’s Islamic sufi preaching manifestes into Islamic preaching practices with a methodical system that emphasizes the hizmet movement with the philanthropist and contemporary media tactics. This praxis exists in its role of producing the golden generation progressively, contributing to an increase in the positive image of Islam and Muslims and moral development of the world community.